Meningkatkan Kepedulian Sosial Melalui Kegiatan Donor Darah Kolaboratif Antara IKT Kartini Batam, Yayasan Buddha Tzu Chi dan Palang Merah Indonesia - Juanna Soehardy; Victor Palapessy; Julia Veronika Larasati; Suryani Suryani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Blood donation activities are an essential form of community service to help meet the growing demand for blood in Indonesia. The collaboration between IKT Kartini Batam, Yayasan Buddha Tzu Chi, and the Indonesian Red Cross (PMI) represents a strategic approach to enhance public social awareness through blood donation. This activity aims to educate the community about the benefits of blood donation and encourage more individuals to participate in this social cause. Held on June 22, 2025, the blood donation event involved 120 donors and successfully raised new awareness among the community, particularly about the importance of blood donation as part of social responsibility. Moreover, the collaboration between the three institutions strengthened existing social networks and enriched the academic community's understanding of community service. The event's evaluation showed positive results with an increase in the number of donors and active community participation, despite some technical challenges related to the number of medical staff. Overall, this activity had a significant impact both socially and academically, and it is expected to continue growing, offering greater benefits to society in the future.